2019
DOI: 10.1038/d41586-019-01157-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic study homes in on height’s heritability mystery

Abstract: Analysis of 20,000 genomes reveals that rare gene variants can help to explain how the trait is inherited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 1 publication
0
6
0
1
Order By: Relevance
“…In order to increase the matching of our populations, we employed summary statistics exclusively derived from European cohorts and European aDNA samples, which in turn increased the predictive power of our results. However, it is important to note that the absolute values of the PRS will not be accurate enough to make any direct conclusions due to the limited heritability of many complex traits, for instance, the heritability of height is 79% and BMI:40% ( Geddes, 2019 ) ( Supplementary Table S2 ). Therefore, we focused on the direction of the changes observed in the PRS within the entire dataset to model the changes in the genetic regulation of these traits within these specific populations.…”
Section: Resultsmentioning
confidence: 99%
“…In order to increase the matching of our populations, we employed summary statistics exclusively derived from European cohorts and European aDNA samples, which in turn increased the predictive power of our results. However, it is important to note that the absolute values of the PRS will not be accurate enough to make any direct conclusions due to the limited heritability of many complex traits, for instance, the heritability of height is 79% and BMI:40% ( Geddes, 2019 ) ( Supplementary Table S2 ). Therefore, we focused on the direction of the changes observed in the PRS within the entire dataset to model the changes in the genetic regulation of these traits within these specific populations.…”
Section: Resultsmentioning
confidence: 99%
“…Dotted line is the trend line, and R 2 is from the bivariate decile mean-decile model to illustrate trend linearity between the PA decile means and the PRS deciles. proposed explanations for this missing (hidden) heritability is the existence of many unidentified common variants with very small effect sizes, rare variants not captured by current genotyping platforms, structural variants, epistatic interactions, gene-environment interactions, or parent-of-origin effects (37,42,43). Interestingly, new research (43) showed that pedigree heritability for height and body mass index seemed to be fully recovered from whole-genome sequence data in the analysis including also rare variants.…”
Section: Discussionmentioning
confidence: 99%
“…proposed explanations for this missing (hidden) heritability is the existence of many unidentified common variants with very small effect sizes, rare variants not captured by current genotyping platforms, structural variants, epistatic interactions, gene-environment interactions, or parent-of-origin effects (37,42,43). Interestingly, new research (43) showed that pedigree heritability for height and body mass index seemed to be fully recovered from whole-genome sequence data in the analysis including also rare variants. These hidden genetic factors may also contribute to the differences between the pedigree and SNP heritabilities for PA in our study, as well as the low explanation rates of the constructed PRS to explain variation in PA. SNP heritabilities obtained from UK Biobank association results using only the effect sizes were statistically significant but low compared with pedigree heritabilities obtained from the FTC subjects using the whole genome and phenotypic information together.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a small portion of the heritabilities can be explained by the discovered common variants [ 2 , 3 ]. Sequencing studies showed that some of the “missing heritability” was attributable to rare variants [ 4 , 5 ]. Complex diseases are usually influenced by genetic factors, environmental factors and the interplay between them.…”
Section: Introductionmentioning
confidence: 99%